PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN DI PT. TUNAS DAIHATSU CABANG BENGKULU - iwin arnova (Universitas Prof.Hazairin,SH Bengkulu, 2020)
This study aims to determine the application of accounting information systems to employee performance has been implemented properly or not at PT. Tunas Daihatsu Bengkulu Branch. The location of this research is at PT. Tunas Daihatsu Bengkulu Branch. The data collection method used in this research is documentation and interview method. While the analysis method used is descriptive qualitative method. The results obtained include the application of accounting information systems to employee performance at PT. Tunas Daihatsu Bengkulu Branch includes1. Human resources or reliable users, 2. Good procedures, 3. Good data, 4. Good software, 5. Information technology infrastructure includes good hardware and adequate communication networks. The conclusion of the research conducted at PT. Tunas Daihatsu Bengkulu Branch The application of accounting information systems to employee performance is good between theory and practice. There are only network constraints which are unstable at times and cannot always be controlled. Therefore, there are several suggestions that can be submitted to PT. Tunas Daihatsu Bengkulu Branch, namely the application of accounting information systems is expected to help various company activities in an effort to increase the success of employee performance, so that employee performance in the company can be optimized, so the effectiveness of accounting information systems as a means of facilitating must continue to be developed and updated regularly following the times and the Company. further improve the quality of accounting information systems such as networks so that companies can carry out their activities effectively and efficiently.